Improving Physical Activity in Hispanics with Diabetes and their Families - Hu, Jie (Public Health Nurs, 2015)
OBJECTIVE: This study examined changes in physical activity among Hispanics with diabetes and their families who received an 8-week diabetes self-management intervention. DESIGN: A quasi-experimental design was used to conduct a secondary analysis of physical activity data from two intervention studies that used the same protocols and measures. SAMPLE: A total of 65 patients and 66 family members participated in the studies. MEASURES: Physical activity was measured with the International Physical Activity Questionnaire (IPAQ) and pedometers. Self-report of physical activity was collected pre- and postintervention, and pedometer data for the 8 weeks of the intervention period. INTERVENTION: The interventions consisted of 8 weeks of educational sessions. RESULTS: IPAQ walking Metabolic Equivalent of Task (MET) minutes per week significantly increased for patients (p < 0.001) and family members (p < 0.001) from pre- to post-intervention as did moderate activity MET-minutes/week for family members (p = 0.004). Based on pedometer steps, the percentage of sedentary patients declined from 38% to 17% over the intervention record; differences in pedometer steps over time were not significant for patients (p = 0.803) or family members (p = 0.144). CONCLUSIONS: Pedometers are a cost effective and user-friendly method of measuring physical activity. Pedometers can also serve as a motivator to help increase physical activity among Hispanics with diabetes and their family members.